ANALYSIS OF AIRPORT AIRSIDE SYSTEM PERFORMANCE USING DISCRETE EVENT SIMULATION MODEL - Juliana Sitanggang, Margaretha
The air transportation demand always increases over time. On the other hand, each airport has different capabilities in serving flight operation. When the demand exceeds the capacity of the airport, there will be a decrease in airside performance. The general way to increase airside performance is to construct a new airside infrastructure. However, this way requires large funds, land availability, and environmental issues. Therefore, this research will find out how to increase airside performance through operational intervention. The analysis was carried out using a microsimulation model that modeled aircraft activity from landing until take-off. The airside system being modeled is the airside system of Kualanamu Airport. Airside performance was measured by throughput and delay. The analysis with a validated model found that significant factors affecting airside performance are flight schedules, aircraft type composition, and ground service activity. The aircraft type that has a significant effect on airside performance is wide-body aircraft. Reducing 1% of the number of wide-body aircraft can reduce queues at the apron and increase airside throughput by 2.31%. Increasing 9% of the number of wide-body aircraft can increase queues at the apron and decrease airside throughput by 23.08%. The ground service activity is affected by the number of ground vehicles. The analysis found that the ground vehicle that number has a significant effect on airside performance is the catering car. Increasing the number of catering car units can increase apron throughput and reduce queues at the apron. However, it is necessary to set flight schedules in such a way as to reduce the queues that occurs before entering the runway.